Blue Carbon Ecosystem Services Through a Vulnerability Lens: Opportunities to Reduce Social Vulnerability in Fishing Communities - Quiros, T. E. Angela L.; Sudo, Kenji; Ramilo, Reynante V.; Garay, Helbert G.; Soniega, Muammar Princess G.; Baloloy, Alvin; Blanco, Ariel; Tamondong, Ayin; Nadaoka, Kazuo; Nakaoka, Masahiro (Frontiers in Marine Science, 2021)
Ecosystem services (ES) are benefits nature provides to humans; these services change in space and time and are largely dependent on context. Coastal habitat that provides key ES are blue carbon ecosystems, namely seagrass and mangroves. One important ES they provide is the provisioning of seafood, which benefits coastal populations with livelihoods and food security. We employed a social-ecological approach that draws from the vulnerability literature for social, ecological, and economic criteria to map ES provision in ten communities on Busuanga Island, Palawan Province, Philippines. We assess the spatial dynamics of ES provision for small-scale fisheries in seagrass and mangroves, in relation to local beneficiaries. Using a mixed-methods approach with ecological assessments of seagrass beds, spatial analysis, landing surveys, household and key informant interviews, we overlaid biophysical variables on social data, mapping sensitivities and adaptive capacities to compare communities’ social vulnerabilities. Spatial analysis revealed healthy blue carbon ecosystems in ten local communities (barangays) as measured by proportion of coastline covered, low patchiness and high continuity along the coastline, and the presence of adjacent habitat. We found seagrass ecosystems were more vulnerable than mangroves. Rural barangays had less exposure and lower sensitivity to blue carbon ecosystem loss than urban barangays. Blue carbon ecosystem fisheries are highly sensitive fisheries, due to their catch composition and low catch per unit effort, with mangrove fisheries having a slightly lower sensitivity than seagrass fisheries due to greater catch per unit effort. Diversified livelihoods and the presence of NGOs and People’s Organizations (POs) increased adaptive capacity and reduced overall vulnerability. We aim to highlight a coastal human community’s relationship with blue carbon ecosystems using context-specific vulnerability criteria. Our site-specific social vulnerability assessment may be adapted for use in other coastal communities within the coral triangle. This work suggests opportunities for conservation interventions to manage local communities’ sensitivities and adaptive capacity around the use of blue carbon ecosystems.